Membangun Tanggung Jawab Karir Siswa Secara Kelompok Melalui Pendekatan Konseling Realitas - Sandra, Rober; Karneli, Yeni; N, Netrawati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Making informed career choices remains a critical challenge for students in the modern era, requiring counseling approaches that foster personal responsibility. This study aims to examine the effectiveness of Reality Therapy interventions in enhancing students' responsibility toward their career decisions. Employing a qualitative approach through a literature review method, this article analyzes relevant academic sources using content analysis techniques. The findings indicate that Reality Therapy consistently promotes self reflection, awareness of choices, and autonomous decision making among students. These results reinforce Choice Theory and offer both theoretical and practical contributions to the development of career guidance services in educational settings. The study concludes that this approach is highly applicable within learner centered educational environments. Further research is recommended through field studies and longitudinal evaluations to assess the sustained impact of such interventions.